DESIGN DESIGN OF MAKING LAND USE AREA MAPS IN SEMATANGBORANG DISTRICT USING QGIS: USING QGIS - Pratama, Sadam Putra; Purnama Sari Dewi, Anggi (Direktorat Riset dan Pengabdian pada Masyarakat Universitas Bina Darma, 2025)
The development of urban areas often results in changes in land use to meet infrastructure needs. In Sematangborang District, Palembang, the challenge of efficient land use requires accurate mapping. Quantum GIS (QGIS) is an effective solution in land use mapping because of its open source nature and spatial analysis capabilities. This research aims to improve the accuracy of land use mapping in the region. This research uses the Geographic Information System (GIS) using QGIS Software for Regional Mapping. Data was obtained through interviews with related agencies and secondary data in the form of Shapefile regional maps from Bappeda and RBI from the Indonesia Geospatial Site. Sematangborang District, which is located 11 km from the center of Palembang City, has an area of 36.97 km2 with four villages. The largest regional distribution is Sukamulya Village (46.70%), followed by Karyamulya (26.69%), Srimulya (18.84%), and Lebong Gajah (7.77%). Mapping using QGIS successfully identified a variety of land uses, including public facilities, settlements, agriculture, and green open spaces. The research succeeded in producing land use maps of various data sources, comprehensive maps succeeded in identifying public facilities, settlements, agriculture, and green open spaces. The results of this mapping can support more effective spatial planning and regional development.